THE PHYSICAL CHARACTERISTICS OF THE ISLAMIC GARDEN AND THE IMPORTANCE OF THE CONCEPT IN MALAYSIA - Md Jani, Haza Hanurhaza; Harun, Nor Zalina (PLANNING MALAYSIA, 2018)
Islamic garden is a traditional garden concept that is significantly related to the history of the Muslim civilization. The first establishment of the concept was in the 7th century through the formation of the Persian Garden. Presently, the idea of the Islamic garden is beginning to be overlooked as the contemporary garden design is becoming a current trend. The situation has given a negative impact towards the implementation of the traditional garden concept. This study is conducted to identify the physical characteristics of the Islamic garden. The first objective is to determine the chronology of the Islamic garden design and, second, to categorize the physical characteristics of the garden according to the level of its importance. Three types of methods are embedded in the study, which are the document analysis, site study, and semi-structured interviews. The method of analysing the data is using the Atlas.ti and Microsoft Excel software. The result gathered are categorized into two important aspects: (1) the movement of the Islamic garden concept in response to the history of the Muslim civilization and (2) the list of the physical characteristic of the Islamic garden. The result is triangulated as to develop an understanding on the list of the significant physical characteristics of the Islamic garden that can be embedded as part of a garden concept in Malaysia. Above and beyond that, the result includes a viewpoint from the National Landscape Department (NLD) on the direction of a garden in Malaysia pertaining to the Islamic garden concept. The input from the session is perceived as necessary as to further develop an understanding of the current level of adaptation of the Islamic garden concept, particularly in Malaysia.